Probing the origin of the unidentified TeV γ-ray source HESS J1702–420 via the surrounding interstellar medium. Issue 3 (7th December 2018) - Lau, J C; Rowell, G; Voisin, F; Blackwell, R; Burton, M G; Braiding, C; Wong, G F; Fukui, Y; Casanova, S
Abstract: The unidentified TeV γ-ray source HESS J1702–420 has no firm associations with any counterparts at other wavelengths. We present an analysis of the interstellar medium using results from the Mopra Southern Galactic Plane CO survey and archival H i data from the Southern Galactic Plane Survey. We find significant components of molecular and atomic gas overlapping the TeV γ-ray source at several velocities along the line of sight, with masses ∼10 2 –10 4 M⊙ and densities up to ∼10 3 cm −3 . Potentially interesting and favourable morphological correspondences between the ISM and the TeV γ-ray emission were found, and in a hadronic scenario, we find that cosmic ray (CR) enhancement values of ∼100 times the local solar values are required to produce the TeV γ-rays. We investigate the separate scenarios in which HESS J1702–420 is powered by the nearby SNR G344.7−0.1, PSRJ1702−4128, and an unknown accelerator. No evidence in the ISM was found to link the SNR with the TeV source. While the morphology of the gas located at the dispersion distance of PSRJ1702−4128 (5.2 kpc, v LSR ∼ −70 km s −1 ) did not discount the possibility of a leptonic origin, the required energetics and the broad and hard TeV spectrum would likely disfavour such a scenario. Given the presence of potentially favourable ISM overlapping HESS J1702–420, we additionally speculate on the plausibility of scenarios involving undetected CR accelerators.